2017
DOI: 10.3389/fneur.2017.00176
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Roles of l-Cysteine in Attenuating Early Brain Injury and Improving Synaptic Density via the CBS/H2S Pathway Following Subarachnoid Hemorrhage in Rats

Abstract: l-Cysteine is a semi-essential amino acid and substrate for cystathionine-β-synthase (CBS) in the central nervous system. We previously reported that NaHS, an H2S donor, significantly alleviated brain damage after subarachnoid hemorrhage (SAH) in rats. However, the potential therapeutic value of l-cysteine and the molecular mechanism supporting these beneficial effects have not been determined. This study was designed to investigate whether l-cysteine could attenuate early brain injury following SAH and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The Bcl-2 family member Bax was markedly up-regulated after OGD/R, which resulted in the release of cytochrome c to the cytosol. Bcl-2 exerts the anti-apoptosis efficiency through inhibiting the function of Bax (30, 31). We found that the OGD/R-induced up-regulation of Bax/Bcl-2 ratio could be reversed by CTs pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bcl-2 family member Bax was markedly up-regulated after OGD/R, which resulted in the release of cytochrome c to the cytosol. Bcl-2 exerts the anti-apoptosis efficiency through inhibiting the function of Bax (30, 31). We found that the OGD/R-induced up-regulation of Bax/Bcl-2 ratio could be reversed by CTs pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we analyzed the activation of Caspase-3 and the degradation of PARP. Cytochrome c release triggers the cleavage of Caspase-3 to activate the Caspase-3 protein, which results in DNA fragmentation and cell apoptosis by cleaving PARP (31, 32). Our data revealed that pre-treatment with CTs prevented the OGD/R-induced increase in cleaved-Caspase-3 and cleaved-PARP.…”
Section: Discussionmentioning
confidence: 99%
“…In several animal model studies, Hcy brought about synaptic dysfunction, oxidative stress, neurochemical imbalance, and apoptosis, resulting in cognitive impairment and neuronal cell death. Thus, an Hcy-induced neurotoxicity model might be suitable for the study of AD ( Ataie et al, 2010a , b , c ; Wei et al, 2014 ; Kamat et al, 2016 ; Li T. et al, 2017 ). Hcy has been shown to modulate glutamate receptors, which leads to various neurotoxic effects.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…It has been reported that BDNF and CREB are closely involved in the impairment seen with brain injury after SAH (Li et al, 2017a,b). BDNF is a neuroprotective protein involved in synaptic plasticity and is known to be the basis of memory processes (Seoane et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An experimental SAH model was made using a double blood injection model according to our previous study (Hu et al, 2016; Li et al, 2017b). Briefly, 3.5% isoflurane was used to induce anesthesia and 2.5% to maintain it.…”
Section: Methodsmentioning
confidence: 99%